Intergenerational transmission of education in Peru: an estimation for the generations born in Peru between 1950 and 1989 - Torres, Javier (2018)
This study estimates the relationship between parents’ years of education and that of their children. We use multiple waves of the national household survey (ENAHO) to cover generations born in Peru between 1950 and 1989. This allows us to analyze in greater detail the general evolution of social mobility in the country, as well as different demographic, geographic and ethnic groups during the second half of the 20th century. We find that the relationship between parents’ education levels and those of their children is positive and significant throughout the period analyzed. Nevertheless, the beta coefficient of intergenerational transmission of education diminishes markedly throughout the decades. It is particularly high (0.74) for those born between 1950 and 1959, but below 0.45 for those born between 1980 and 1989. Furthermore, there are great disparities and irregular trends depending on the groups analyzed. There is a greater reduction of the beta coefficient in the case of female heads than of male heads. Household heads self-identified as “mestizo” and born between 1980 and 1989 have a beta coefficient of 0.41; while those self-identified as “negro o mulato”, born within the same time frame, show a beta coefficient of 0.59. Household heads self-identified as “negro o mulato” experience the least reduction of the beta coefficient throughout the years